1994
DOI: 10.1038/bjc.1994.160
|View full text |Cite
|
Sign up to set email alerts
|

CGP 55398, a liposomal Ge(IV) phthalocyanine bearing two axially ligated cholesterol moieties: a new potential agent for photodynamic therapy of tumours

Abstract: Ge(IV) phthalocyanine (GePc) with two axially ligated cholesterol moieties was prepared by chemical synthesis and incorporated in a monomeric state into small unilamellar liposomes (CGP 55398). Upon photoexcitation with light wavelengths around its intense absorption peak at 680 nm, GePc shows an efficient photosensitising activity towards biological substrates through a mechanism which largely involves the intermediacy of singlet oxygen. GePc injected systemically into mice bearing an intramuscularly implante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 31 publications
3
25
0
Order By: Relevance
“…The therapeutic efficiency is similar to that observed for the unsubstituted Zn-phthalocyanine (Reddi et al, 1990), but higher than that observed for other phthalocyanine derivatives (Segalla et al, 1994) tested in the same tumour model. The higher PDT efficiency exhibited by the bis(siloxyhexyl)derivative may reflect the slightly larger concentration of this GePc in the tumour at the time of irradiation.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The therapeutic efficiency is similar to that observed for the unsubstituted Zn-phthalocyanine (Reddi et al, 1990), but higher than that observed for other phthalocyanine derivatives (Segalla et al, 1994) tested in the same tumour model. The higher PDT efficiency exhibited by the bis(siloxyhexyl)derivative may reflect the slightly larger concentration of this GePc in the tumour at the time of irradiation.…”
Section: Discussionsupporting
confidence: 81%
“…In general, the muscle takes up small amounts of photosensitisers and, as a consequence, tumour/peritumoral tissue ratios are higher for intramuscularly implanted tumours than those for tumours implanted in other anatomical sites with the exception of brain tumours (Tralau et al, 1987). However, the levels of selectivity thus reached are at least similar to those found for other second-generation photosensitisers delivered in liposomes and tested in the same tumour model (Reddi et al, 1990;Segalla et al, 1994) and markedly larger than that typical of Photofrin (Dougherty, 1987). A similar enhancement of the tumour-localising efficiency has been observed upon lowering the number of sulphonate substituents in the peripheral positions of the phthalocyanine macrocycle (Korbelik, 1993); less polar phthalocyanines are endowed with a higher tendency to penetrate malignant cells, thereby shifting the mechanism of photoinduced tumour necrosis from a prevailing vascular damage to a direct inactivation of neoplastic cells (Milanesi et al, 1987;Henderson and Bellnier, 1989).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our findings on the biodistribution of Cremophor-delivered ZnODPc in Balb/c mice bearing an intramuscularly transplanted MS-2 fibrosarcoma are in good agreement with those obtained for other phthalocyanines in the same animal model (Segalla et al, 1994;Soncin et al, 1995b) with regard to the timing and amount of maximal accumulation in the tumour (15-24 h after i.v. injection), the rate of plasma clearance and the high concentrations recovered from liver Figure 8 Tumour specimen obtained at 6 h after PDT ( x 30 000).…”
Section: Discussionsupporting
confidence: 88%
“…The resulting oil was washed with 20 mL of pentane (SDS) and 20 mL of acetone-water (SDS) solution (1:1 vol. [54,55].…”
Section: Synthesis Of the Tri-n-hexylsiloxy Aluminum Phthalocyanine mentioning
confidence: 97%